Returning to School After a Life-Altering Disruption: A Qualitative Study of Childhood Hematologic Malignancies Survivors and Parents. - Huang, Hsiu-Mei; Yeh, Ting-Chi (Journal of School Nursing, 2026)
After completing treatment, hematologic malignancy survivors face a critical phase of reintegrating into society. This study explored how survivors and their parents gradually returned to daily life, using grounded theory and in-depth interviews with 13 survivors and 16 parents. Data were analyzed revealed that hematologic malignancy survivors and their parents needed time to gradually return to daily life after a life-altering disruption after completing treatment. This process includes three categories: (1) adjusting to achievable learning goals, (2) incrementally expanding social relationships, and (3) strengthening daily life skills. As they return to daily life, both hematologic malignancy survivors and their parents need to adjust their mindset and pace to gradually adapt to the challenges they encounter. In the future, school nurses and oncology nurses can collaborate to design appropriate return-to-school plans to assist these children in their adaptation.